2022
DOI: 10.1073/pnas.2108046119
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-14 motors participate in a force balance at microtubule plus-ends to regulate dynamic instability

Abstract: Kinesin-14 molecular motors represent an essential class of proteins that bind microtubules and walk toward their minus-ends. Previous studies have described important roles for Kinesin-14 motors at microtubule minus-ends, but their role in regulating plus-end dynamics remains controversial. Kinesin-14 motors have been shown to bind the EB family of microtubule plus-end binding proteins, suggesting that these minus-end–directed motors could interact with growing microtubule plus-ends. In this work, we explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…To complete the system, we added microtubule tip tracking protein EB3, which is known to bind HSET in a way that makes microtubule binding domains on both EB3 and HSET available for engaging microtubules. 47,48 We verified this interaction and confirmed that it allowed HSET to transport EB away from microtubule tips on individual microtubules (Figure S2A/Video S2). Unexpectedly, however, when both minus-end directed motor and tip tracker were present in our assay, we observed not only pulling, but also pushing forces as was indicated by the increase in the distance between the beads (Figure 1C,D and Figure S1).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…To complete the system, we added microtubule tip tracking protein EB3, which is known to bind HSET in a way that makes microtubule binding domains on both EB3 and HSET available for engaging microtubules. 47,48 We verified this interaction and confirmed that it allowed HSET to transport EB away from microtubule tips on individual microtubules (Figure S2A/Video S2). Unexpectedly, however, when both minus-end directed motor and tip tracker were present in our assay, we observed not only pulling, but also pushing forces as was indicated by the increase in the distance between the beads (Figure 1C,D and Figure S1).…”
Section: Resultssupporting
confidence: 56%
“…We showed that a simple system consisting of a single minus-end directed motor that acts synergetically with growing dynamic microtubules via the action of tip tracking EB proteins can perform both, separation of the two microtubule asters and stabilization of their bipolar organization. HSET is known to affect the aster formation, the spindle size and to interact with EB proteins 15,17,18,48 , and EBs are known to make multivalent condensates and facilitate transport 38,39,45,46 . Here, we reveal how the combined EB/HSET/microtubule system allows harnessing microtubule forces that stabilize the bipolar organization of two asters, which is not achievable by mechanisms used by these molecules alone.…”
Section: Discussionmentioning
confidence: 99%
“…Tau helps in MT bundling and promotes its growth and inhibits its shrinkage by regulating the labile domain of MT [ 20 ]. A recent study by Mecak et al [ 21 ] proved the involvement of kinesin-14 motor proteins in regulating the dynamic instability of MTs. The MT cytoskeleton is constantly exposed to external mechanical forces arising from active ongoing processes within or outside the cell.…”
Section: Neuronal Microtubules: Structural Overview and Assemblymentioning
confidence: 99%
“…The activity of Kar3 heterodimers on MTs was first described as a minus-end-directed translocation with low processivity ( Endow et al, 1994 ), a property common to other kinesin-14 family members. Subsequent Kar3 studies provided evidence for its potential to switch between plus-end- and minus-end-directed movement ( Molodtsov et al, 2016 ), or to stably associate with a growing plus-end ( Sproul et al, 2005 ), possibly when in complex with Bim1, the budding yeast homolog of MAPRE family members (also known as EB1) ( Kornakov et al, 2020 ; Ogren et al, 2022 ; Sproul et al, 2005 ). In addition, although early work with Kar3 provided evidence for plus-end depolymerase activity ( Sproul et al, 2005 ), later work failed to document this activity ( Mieck et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%